Incidence of cardiac arrest and related factors in a multi-center thai university-based surgical intensive care units study (THAI-SICU study) - Chanthawong S. (2017)
© 2016, Medical Association of Thailand. All rights reserved. Objective: To describe the incidences, outcomes and determine the risk factor(s) of cardiac arrest in surgical intensive care unit (SICU). Material and Method: We collected data between April 2011 and January 2013. The case record form (CRF) included the CRF 1 (admission, daily screening and discharge data) and the CRF 2 for cardiac arrest events. The patients were followedup until discharge from SICU or for up to 28 days after admission in SICU. Results: The incidence of cardiac arrest in SICU was 226 in 4,652 patients (4.9%). The APACHE II score at the day with cardiac arrest were 24.1. Initial monitor rhythm during cardiac was asystole (35.4%), bradycardia (22.6%) and pulseless electrical activity (14.6%). The main cause was poor patient condition before admission (51.3%). Most of the cardiac arrest patients (73.9%) had antecedents within 24 hour and the most common antecedents were hypotension, metabolic disturbances and sepsis and/or septic shock. The overall return of spontaneous circulation rate was 23.5%. At hospital discharge, the mortality rate (91.6%) was statistically different between the cardiac arrest and non-cardiac arrest group (p < 0.001). The Acute Physiologic and Chronic Health Evaluation II score (APACHE II score) (Odds ratio, (OR 1.15, 95% CI 1.11-1.19, p < 0.001), Sequential Organ Failure Assessment score (SOFA score) (OR 1.12, 95% CI 1.03-1.20, p = 0.005) and American Society of Anesthesiologists physical status physical status (ASA PS) > 3 (OR 2.32, 95% CI 1.33-4.04, p = 0.003) were significantly risk factors for cardiac arrest. Conclusion: Cardiac arrest in the SICU was uncommon. Initial non-shockable rhythms were common and mostly had antecedents before cardiac arrest. The APACHE II score, SOFA score and ASA PS > 3 were independent risk factors for cardiac arrest in SICU.